Effect of dual task exercise on dynamic balance in futsal player with functional ankle instability - Fortunella Levyana; Anita Faradilla Rahim; Dimas Sondang Irawan (Physical Therapy Journal of Indonesia, 2024)
Background: Recurrent ankle sprains are typically caused by an athlete performing two or more duties at the same time. At least one task performance and dynamic balance are carried out in most athletic performances. This study aimed to determine an intervention that involves dual tasks for futsal players with functional ankle instability (FAI) and to investigate the effect of the exercise on dynamic balance and different characteristics of players. Methods: The research was quasi-experimental, with a non-equivalent control group design. Thirty futsal players with FAI were recruited, as identified by the Identification of Functional Ankle Instability questionnaire. The participants were separated into experimental (n=16) and control (n=14) groups. The experimental group did plyometric exercises and cognitive activities (serial three or serial seven) for 15 minutes each, three times a week for six weeks. In contrast, the control group performed only plyometric exercises. The Y-Balance Test was used to measure dynamic balance. Participants were tested again six weeks later. Results: The experimental group showed more significant improvement than the controls. Compared before and after intervention in each group, the dynamic balance was substantially increased (p<0.05). Following the intervention, no statistically significant difference was seen between the two groups (p>0.05). Conclusions: In this article, we outlined the potential use of dual-task exercise (DTE) in the athlete population to support athletic performance and provide more insights to implement in injury prevention. We need further research to clarify the optimum time to make significant improvements with DTE.